(untitled) (Revista de Psicología, 2025)
The research aimed to compare the use of learning strategies among repeating and non-repeating high school students in a public school in Santander, Colombia. A quantitative methodology was employed, involving 90 students selected through a census sampling method: 28 were repeating students (M age = 15.32, σ = 1.54) and 62 were non-repeating students (M age = 15.06, σ = 1.26). The ACRA Scales were applied, which measure the use of learning strategies for acquisition, encoding, retrieval, and information processing support. It was found that non-repeating students use all learning strategies at a high level, while repeating students use retrieval and support strategies highly and acquisition and encoding strategies moderately. Additionally, it was evident that the support strategy was the most utilized by both groups, with the difference being that in non-repeating students it is related to intrinsic motivational aspects, whereas in repeating students it is associated with the pursuit of immediate rewards. To identify significant differences in the use of strategies between the two groups, the Mann-Whitney U test was employed. The results revealed significant differences in the use of learning strategies.